2001
DOI: 10.1177/01939450122045177
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Nurses’ Self-Concept

Abstract: Little is known of nurses' self-concept in light of their professional identity or as working adults. This article explores the development and rigorous testing of a new self-concept instrument designed specifically for nurses. The new measure is based on the self-concept measurement theory of Shavelson, Hubner, and Stanton. An expert panel was used to critique and aid refinement of the measure. The dimensions of nurses' self-concept were measured in six scales: General Nursing, Care, Staff Relations, Communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
119
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 12 publications
6
119
1
3
Order By: Relevance
“…This is particularly important to the future of nursing as the profession has been called on the profession to lead change in advancing health policy (Institute of Medicine, 2011). Yet, this study found that leadership was the weakest aspect of the students' professional self-concept, mirroring findings from studies of practicing nurses (Cowin, 2001;Cowin, & Hengstberger-Sims, 2006;Hensel, 2011). If this is true perhaps the greatest challenge for the profession is not how to teach professional values, but how to recruit pre-licensure candidates who will best contribute to nursing's preferred future.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…This is particularly important to the future of nursing as the profession has been called on the profession to lead change in advancing health policy (Institute of Medicine, 2011). Yet, this study found that leadership was the weakest aspect of the students' professional self-concept, mirroring findings from studies of practicing nurses (Cowin, 2001;Cowin, & Hengstberger-Sims, 2006;Hensel, 2011). If this is true perhaps the greatest challenge for the profession is not how to teach professional values, but how to recruit pre-licensure candidates who will best contribute to nursing's preferred future.…”
Section: Discussionsupporting
confidence: 64%
“…Survey data were collected in the fall semester of 2011 using the Nurse SelfConcept Questionnaire (NSCQ) and the Student Alcohol Questionnaire (SAQ). Created in Australia, the NSCQ has 36 items on 8-point ordinal response scales that measure the six dimensions of a nurse's professional self-concept described by Cowin (2001). The NSCQ has theoretical and construct validity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A self-concept instrument is based on a multidimensional and dynamic framework (Cowin, 2001;Marsh and Craven, 2006). This multidimensional conceptual framework of self-concept involves knowledge, care, leadership, satisfaction, communication, and staff relations (Angel et al, 2012;Arthur, 1995;Arthur and Thorne, 1998;Cowin, 2001). Nurses' professional self-concept not only reflects nurses' selfperception of professional competencies but also indicates the skills that are essential for patient care (Milisen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%